The Investigation of Teaching Listening Skills in Chinese colleges - Chenyang Zhang (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2021)
Abstract: English as an international language has received the increasing attention of Chinese educators and students. For college students, the proficiency of English could help them to acquire a desirable job or receive higher education. With attention to listening, it is an indispensable channel for students to possess and master language knowledge. However, college students usually show weak performance in listening. More seriously, they tend to feel nervous and anxious in the formal listening tests. Given this issue, through the exploration of the pedagogic reasons, this study aims to support a suitable teaching and learning model- the integrative listening model, in which three listening strategies will be highlighted, namely, bottom-up, top-down and metacognitive approaches.